Regional, rural and remote schools as a career choice for Australian pre-service teachers: A decision tree analysis - Harris, Marnie; Vernon, Lynette; Rhodes, David; Gray, Christina (Issues in educational research, 2024)
Professional experience is crucial in initial teacher education, enabling pre-service teachers to develop their skills in authentic classroom settings. However, with most Australian initial teacher education institutions located in metropolitan areas, few pre- service teachers undertake experiences in regional, rural or remote (RRR) schools, presenting challenges in preparing, attracting, and retaining teachers in these areas. Despite initiatives to address RRR teacher shortages, little progress has been made. Our study aimed to identify enablers and barriers for primary pre-service teachers during RRR professional experiences to address workforce shortages. Data were quantitatively analysed using multi-model classification-decision tree analysis. The analysis revealed professional growth and skill development during RRR professional experiences were the most influential factors in pre-service teachers' decisions to pursue RRR teaching positions. Notably, shorter, well-designed professional experiences were found to be as effective as longer placements in promoting RRR teaching careers. Other factors, such as social connections, support networks, and feelings of isolation, also played a role in pre- service teachers' decisions. The research findings illuminate and strengthen understandings for initial teacher education institutions to promote enablers and mitigate identified barriers to encourage more pre-service teachers to develop positive attitudes about and a willingness to relocate to RRR schools and communities upon graduation.